A Novel Design Method for Chip Flute of Indexable Insert Drill Used at Large Drilling Depth - Aisheng Jiang; Zhanqiang Liu; Jinfu Zhao (Metals)
The design of the chip flute in indexable insert drills significantly influences chip removal efficiency, drill diameter deflection, and drill deformation in the metal drilling process, which are crucial for maintaining drill stability and minimizing deviations in the diameter of the drilled hole. However, traditional chip flute designs fail to meet production standards when drilling deep holes in 42CrMo, particularly at depths reaching up to seven times the hole diameter. This study introduces an innovative optimization method for the chip flute design of indexable insert drills specifically intended for metal deep-cutting applications, which involves refining both the cross-sectional and circumferential profiles of the chip flute. A novel combined cross-section for the chip flute was developed and tested against the conventional double U-profile in drilling experiments on 42CrMo. Based on the chip shape of the inner and outer inserts, the inner insert flute section is designed into a U-shaped section and the outer insert flute section is designed into trapezoidal section, respectively, so as to increase the proportion of the effective chip removal area in the chip flute, which reduces the chip flute section area and increases the core thickness of the tool holder. Additionally, the circumferential profile was enhanced through orthogonal simulation experiments. The findings revealed that the drill diameter deflection using the newly designed combined cross-section was reduced by 21.76% compared to the traditional double U-profile in the metal drilling process. The indexable insert drill featuring this optimized chip flute configuration exhibited significant improvements in the drill diameter deflection, drill deformation, and drilled hole diameter accuracy, outperforming the standard drill design.